THE BENEFITS OF EQUESTRIAN TOURISM DEVELOPMENT AND ITS INTERRACTION WITH THE TERRITORY - Ivanova , D. Lyubov (Europa del Este Unida, 2021)
The equestrian industry is an economic sector that encompasses all goods and services related to horses and the activities carried out by them in order to meet the needs of the final users. The popularity of equestrian tourism is now growing rapidly around the world. Horseback riding is known and popular in almost all of Europe, but few countries have developed equestrian tourism until 1980. In equestrian tourism, the main idea is walks in the fresh air, in an open nature, love and care for the horse. And most importantly, it is a kind of sport, available for all ages without restriction. It is the love of the horse that becomes the main reason for laying the foundations of the horse routes.